Partisipasi Citizen Journalism dalam Mengembangkan Informasi Seni Ketangkasan Domba Garut - Tannia Meirina Anwar; Atie Rachmiatie (UNISBA Press, 2023)
Abstract.This research is motivated by citizen journalism or known as Citizen journalism has an active role in the process of collecting, reporting, analyzing, and disseminating news and information owned. The purpose of this study was to determine the contribution, role, and expectations of citizen journalism in the development of Sundanese cultural information, the art of dexterity of the Garut sheep on social media Instagram. This relates to the nature of humanity that needs and is accustomed to telling